Cognitive Features in Adults with Autism Spectrum Disorder, Diagnosed in Childhood without Intellectual Disabilities - M.M. Ivanova; L.G. Borodina (Moscow State University of Psychology and Education, 2021)
A study of cognitive features in autism spectrum disorders (ASD) adults without intellectual disabilities involved 20 participants diagnosed in childhood with Asperger's syndrome and atypical autism, 20 respondents with schizophrenia spectrum disorders, and 20 neurotypical adults. Following psychological instruments were used "Comparison of concepts" (15 pairs of words), "Fifth extra", "Fourth extra". Tools were modified to identify formal thinking disorders in adults. A free-form story was also used. It was found that answers in a sample of adults with ASD, diagnosed in childhood are significantly more often indicating a distortion of the generalization process, rather than answers in a group of neurotypical participants. At the same time, this trend in the autism group is significantly lower than in the schizophrenia group. Following trend also revealed - answers identifying a decrease in the level of generalization and disorders of the motivational cognitive component. This trend is very similar in the groups of autism and schizophrenia, but significantly exceeds in the group of neurotypical subjects